ANTIMICROBIAL ACTIVITY AND PHYTOCHEMICAL STUDY OF MEDICINAL PLANT ALPINIA GALANGA - Kr, Beula Rani; Sk, Sundar; M, Murugan (Asian Journal of Pharmaceutical and Clinical Research, 2016)
Objective: The study was undertaken to evaluate the antimicrobial activity and phytochemical constituents of the medicinal plant Alpinia galanga. Methods: The plant samples were collected from the places of Mandaikadu, Kanyakumari District, Tamil Nadu, India. Plant extracts were prepared from the dried leaf powder using different solvents include acetone, chloroform, diethyl ether, ethanol, and distilled water. Initially, antimicrobial activities of the plant extracts were tested by agar well diffusion method against four bacterial, viz., Escherichia coli, Klebsiella pneumonia, Bacillus cereus, and Staphylococcus aureus and two fungal pathogens, viz., Aspergillus niger and Penicillium chrysogenum. Further, the plant extracts were screened for phytochemical constituents by standard protocols. Results: In this study, the entire bacterial pathogens have inhibited by acetone, chloroform, diethyl ether, and ethanol extracts. In phytochemical screening tests, the plant extracts showed positive results for carbohydrates, amino acid, chloride, alkaloids, flavonoids, phenols, and terpenoids. Conclusion: This study reveals the continuation of antimicrobial components in the medicinal plant A. galanga. Keywords: Alpinia galanga, Phytochemical, Antimicrobial activity and plant extracts.